Polyimide diaphragm for semi-solid lithium battery and preparation method of polyimide diaphragm
By using polypropylene-based film and fast ion conductor-modified polyimide slurry in semi-solid lithium battery separators, the lithium battery separators are solved by low lithium ion conductors and high interface impedance. The problem of this system improves the charging speed and safety of the battery, and achieves higher energy density and heat resistance.
Patent Information
- Application Number
- CN202411447641.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The lithium-ion conductivity of semi-solid lithium battery separators is low, which affects the charging speed and safety of the battery. In addition, the interface impedance of the traditional separators is high, making it difficult to meet the needs of high energy density and safety.
Using polypropylene-based film as the matrix, a gel polyimide coating layer is formed by spraying fast ion conductor modified polyimide slurry to improve lithium ion conductor and interface contact, reduce interface impedance, and prepare high performance polyimide diaphragm.
It significantly improves the ionic conductivity of lithium batteries, enhances the heat resistance and safety of the membrane, reduces the electrode interface impedance, and improves the overall performance and safety of the battery.
Smart Images

Figure CN119324296A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery separators, and in particular relates to a polyimide separator for a semi-solid lithium battery and a preparation method thereof. Background Art
[0002] As a recognized ideal energy storage element, lithium-ion batteries have made significant progress in recent decades and have made outstanding contributions to large-scale energy storage fields such as portable electronic products and electric vehicles. With the widespread application of lithium-ion batteries, battery safety and high energy density have become increasingly important and challenging. As a physical barrier that isolates the positive and negative electrodes of the battery and accommodates electrolytes for ion shuttle, the separator needs to have the following characteristics for battery safety and high energy density: light and thin, no obvious shrinkage at high temperatures, good mechanical strength, and good affinity with the electrolyte.
[0003] Although traditional liquid lithium batteries have high ionic conductivity, liquid electrolytes have a low boiling point and are prone to leakage, which can easily cause lithium dendrite growth. They have relatively low energy density and are prone to safety issues. Solid electrolytes provide a good opportunity to solve safety problems and prevent the growth of lithium dendrites, but they have poor interface stability, high interface impedance, complex production processes, and high manufacturing costs, making them difficult to commercialize on a large scale. Semi-solid batteries perform better than liquid batteries but worse than all-solid batteries, with better safety, higher energy density, longer cycle life, wider operating temperature range, and resistance to extrusion and vibration.
[0004] At present, semi-solid battery separators are mainly made of wet polyolefin films coated with ceramic materials. The coating of ceramic materials improves the heat resistance of the separator, enhances the puncture resistance of the separator, and improves the safety of battery use. However, there are defects such as large interface contact impedance between battery electrodes and separators and relatively low lithium ion conductivity, which need to be further improved. Summary of the invention
[0005] One of the purposes of the present invention is to provide a polyimide separator for a semi-solid lithium battery to solve the problem of relatively low lithium ion conductivity;
[0006] A second object of the present invention is to provide a method for preparing a polyimide separator for a semi-solid lithium battery.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In the first aspect, a polyimide separator for a semi-solid lithium battery comprises a polypropylene base film and a gel polyimide coating layer disposed on both sides of the polypropylene base film, wherein the gel polyimide coating layer is made by spraying a fast ion conductor modified polyimide slurry;
[0009] The fast ion conductor modified polyimide slurry comprises the following components in parts by weight:
[0010] 3.5-4.5 parts of thermoplastic polyimide;
[0011] 1-3 parts of lithium bis(trifluoromethanesulfonyl)imide;
[0012] Fast ion conductor lithium lanthanum zirconium oxide 0.8-1.2 parts;
[0013] Sulfolane 35-45 parts.
[0014] Furthermore, the polypropylene-based film has a melt flow rate (MI) of 0.3-0.5 g / 10 min, a tensile strength of 200-240 MPa, a pore size of 50-110 nm, and a porosity of 50-55%.
[0015] Furthermore, the chemical structural formula of the thermoplastic polyimide is Formula I:
[0016]
[0017] Where x = 60-80%;
[0018] Where R is Any one of the following, wherein n is any integer between 0 and 5, and R1 and R2 are -H or -CH3.
[0019] In a second aspect, a method for preparing a polyimide separator for a semi-solid lithium battery comprises the following steps:
[0020] Step 1, preparing a fast ion conductor modified polyimide slurry: adding thermoplastic polyimide to cyclopentane sulfone under stirring conditions, reacting at 140-160° C. for 1-3 hours, then sequentially adding lithium bis(trifluoromethanesulfonyl)imide and fast ion conductor lithium lanthanum zirconium oxide, and continuing the reaction for 1-3 hours to obtain a fast ion conductor modified polyimide slurry;
[0021] Step 2, performing corona treatment on the polypropylene base film;
[0022] Step 3: spray the fast ion conductor modified polyimide slurry on the surface of the polypropylene base film after corona treatment, and vacuum dry it to obtain a polyimide separator for a gel semi-solid lithium battery.
[0023] Furthermore, the preparation method of the thermoplastic polyimide comprises the following steps:
[0024] S1. Preparation of amino-terminated polyamic acid prepolymer A:
[0025] Under nitrogen protection and ≤5°C, 4,4'-diaminodiphenyl ether and pyromellitic anhydride were added to N,N-dimethylacetamide (DMA) in sequence to obtain a low polymerization degree amino-terminated polyamic acid prepolymer A, the chemical structure of which is Formula II:
[0026]
[0027] Furthermore, the molar ratio of the anhydride in pyromellitic anhydride to the amino group in 4,4'-diaminodiphenyl ether is 1:(1.2-1.5), and the solid content in the reaction system is 25-35%.
[0028] S2. Preparation of anhydride-terminated polyamic acid prepolymer B:
[0029] Under nitrogen protection and ≤5°C, 4,4'-diaminodiphenyl ether and diphenyl diglycoside compound are added to N,N-dimethylacetamide in sequence to react to obtain a low polymerization degree terminal anhydride polyamic acid prepolymer; the chemical structure is Formula III:
[0030]
[0031]
[0032] Furthermore, the chemical structural formula of the diphenyl diglycoside compound is Formula IV:
[0033] Where R is Any one of the following, wherein n is any integer between 0 and 5, and R1 and R2 are -H or -CH3.
[0034] Furthermore, the molar ratio of the acid anhydride in the diphenyl diglycoside compound to the amino group in 4,4'-diaminodiphenyl ether is 1:(1.2-1.5), and the solid content in the reaction system is 25-35%.
[0035] S3. Preparation of polyamic acid solution:
[0036] The amino-terminated polyamic acid prepolymer A and the anhydride-terminated polyamic acid prepolymer B are uniformly mixed and subjected to condensation reaction to obtain a polyamic acid solution, wherein the chemical structural formula of the polyamic acid is Formula V;
[0037]
[0038] S4. Preparation of thermoplastic polyimide:
[0039] Under stirring conditions at room temperature (25-30°C), add an imidization agent to the polyamic acid solution, mix well, raise the temperature to 35-45°C and continue the reaction for 15-20h to obtain a polyimide solution, cool to room temperature, add ethanol for precipitation, collect the precipitate, and vacuum dry to obtain a thermoplastic polyimide.
[0040] Furthermore, the imidization reagent is composed of acetic anhydride and triethylamine mixed in a molar ratio of 1:1.
[0041] Furthermore, the molar ratio of the imidization agent to the total amount of 4,4'-diaminodiphenyl ether is 1:(0.2-0.8).
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The present invention utilizes thermoplastic polyimide with a specific structure, introduces fast ion conductor lithium lanthanum zirconium oxide (LLZO) and lithium bis(trifluoromethanesulfonyl imide) into the thermoplastic polyimide, increases the ionic conductivity of the electrolyte, improves the charging speed of the lithium battery, and hinders the growth of lithium dendrites. The thermoplastic polyimide is prepared into a slurry and sprayed on the surface of a dry-stretched polypropylene porous membrane base film to obtain a gel polyimide composite diaphragm with excellent comprehensive performance.
[0044] 2. In the present invention, the obtained thermoplastic polyimide has a long-term heat resistance of up to 240°C and can quickly form a gel in a typical lithium-ion battery liquid electrolyte; the gel polyimide coating layer can greatly improve the heat resistance of the diaphragm and enhance the safety of the lithium battery, and the gel polyimide is in close contact with the electrode, which greatly reduces the interface impedance and reduces the amount of liquid electrolyte added during the preparation of the lithium battery, thereby meeting the preparation requirements of the semi-solid battery.
[0045] 3. The present invention replaces part of pyromellitic anhydride with diphenyl diglycoside compound, introduces structures such as ketone, ether, methylene chain into the molecular chain of polyimide, increases the flexibility of molecular chain, and improves the adhesion and toughness of polyimide. Design molecular structure, control the type (anhydride or amino group) and content of end group, synthesize polyamic acid prepolymer with amino group at the end and polyamic acid prepolymer with anhydride at the end (B1, B2, B3, etc.), by means of stepwise polymerization strategy, add A and B substances step by step, control the molar ratio of A and B substances and polymerization reaction conditions, and obtain polyamic acid with different structures and molecular weights. Slowly add imidization reagent composed of dehydrating agent acetic anhydride and catalyst triethylamine into the obtained polyamic acid solution, carry out chemical imidization, and obtain thermoplastic polyimide with different structures and molecular weights. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The present invention will be further described below in conjunction with the accompanying drawings.
[0047] Figure 1 It is a schematic diagram of the preparation process of the thermoplastic polyimide of the present invention. DETAILED DESCRIPTION
[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The schematic diagram of the preparation process of the thermoplastic polyimide in the following examples and comparative examples is as follows: Figure 1 shown.
[0050] Example 1
[0051] A thermoplastic polyimide, the chemical structure of which is Formula VI:
[0052]
[0053] Mode Where x=75%.
[0054] The preparation method of the thermoplastic polyimide comprises the following steps:
[0055] S1. Preparation of amino-terminated polyamic acid prepolymer A:
[0056] Using DMA as solvent, under nitrogen protection and at ≤5°C, add 4,4'-diaminodiphenyl ether to DMA, and after it is completely dissolved, add pyromellitic anhydride, the molar ratio of the anhydride in pyromellitic anhydride to the amino group in 4,4'-diaminodiphenyl ether is 1:1.4, and the solid content in the reaction system is 30%; react for 4h to obtain a low polymerization degree terminal amino polyamic acid prepolymer A;
[0057] S2. Preparation of anhydride-terminated polyamic acid prepolymer B:
[0058] Using DMA as solvent, under nitrogen protection and at ≤5°C, add 4,4'-diaminodiphenyl ether to DMA. After it is completely dissolved, add 4,4'-oxydiphthalic anhydride. The molar ratio of the anhydride in 4,4'-oxydiphthalic anhydride to the amino group in 4,4'-diaminodiphenyl ether is 1:1.4, and the solid content in the reaction system is 30%; the reaction obtains a low polymerization degree terminal anhydride polyamic acid prepolymer B;
[0059] S3. Preparation of polyamic acid solution:
[0060] The amino-terminated polyamic acid prepolymer A and the anhydride-terminated polyamic acid prepolymer B are uniformly mixed in proportion and subjected to condensation reaction to obtain a polyamic acid solution;
[0061] S4. Preparation of thermoplastic polyimide:
[0062] Under stirring conditions at room temperature and 200 rpm, an imidization reagent (composed of acetic anhydride and triethylamine mixed in a molar ratio of 1:1) was added to the polyamic acid solution, and the molar ratio of the imidization reagent to the total amount of 4,4'-diaminodiphenyl ether was 1:0.5. After mixing evenly, the temperature was raised to 40°C and the reaction was continued for 18 hours to obtain a polyimide solution, which was cooled to room temperature, ethanol was added for precipitation, the precipitate was collected, and vacuum dried to obtain a thermoplastic polyimide.
[0063] Embodiment 2-4
[0064] The chemical structural formulas of the thermoplastic polyimide in Examples 2-4 are respectively Formula VII, Formula VIII, and Formula IX, as shown in Table 1;
[0065] The preparation method of the thermoplastic polyimide described in Examples 2-4 is different from that in Example 1 in that the diphenyl dianhydride compound in S2 is 3,3',4.4'-tetrabenzophenone tetracarboxylic dianhydride. 2,2-Diphenylpropane-3,4,3',4'-tetracarboxylic dianhydride 3,3',4.4'-Biphenyltetracarboxylic acid The remaining steps and parameters remain the same.
[0066] Table 1
[0067]
[0068]
[0069] Example 5
[0070] A method for preparing a polyimide separator for a semi-solid lithium battery comprises the following steps:
[0071] Step 1, preparing a fast ion conductor modified polyimide slurry: adding 4 parts of the thermoplastic polyimide prepared in Example 1 to 40 parts of sulfolane under stirring at 200 rpm, reacting at 150° C. for 2 h, then adding 2 parts of lithium bis(trifluoromethanesulfonyl)imide and 1 part of fast ion conductor lithium lanthanum zirconium oxide in sequence, and continuing the reaction for 2 h to obtain a fast ion conductor modified polyimide slurry;
[0072] Step 2, using a polypropylene base film with MI=0.4g / 10min, tensile strength of 220MPa, pore size of 80nm, and porosity of 52%, and performing corona treatment on its surface;
[0073] Step 3: spray the fast ion conductor modified polyimide slurry on the surface of the polypropylene base film after corona treatment, and vacuum dry it to obtain a polyimide separator for a gel semi-solid lithium battery.
[0074] Example 6
[0075] A method for preparing a polyimide separator for a semi-solid lithium battery is different from that of Example 5 in that the thermoplastic polyimide prepared in Example 2 is used in step 1, and the remaining steps and parameters remain the same.
[0076] Example 7
[0077] A method for preparing a polyimide separator for a semi-solid lithium battery is different from that of Example 5 in that the thermoplastic polyimide prepared in Example 3 is used in step 1, and the remaining steps and parameters remain the same.
[0078] Example 8
[0079] A method for preparing a polyimide separator for a semi-solid lithium battery is different from that of Example 5 in that the thermoplastic polyimide prepared in Example 4 is used in step 1, and the remaining steps and parameters remain the same.
[0080] Comparative Example 1
[0081] A method for preparing polyimide, which differs from Example 1 in that 4,4'-oxydiphthalic anhydride in S2 is replaced by an equal amount of pyromellitic anhydride, and the other steps and parameters remain the same.
[0082] Comparative Example 2
[0083] A method for preparing polyimide, which is different from Example 1 in that the pyromellitic anhydride in S1 is replaced by an equal amount of 4,4'-oxydiphthalic anhydride, and the other steps and parameters remain the same.
[0084] Comparative Example 3
[0085] A method for preparing a polyimide separator for a lithium battery is different from that of Example 5 in that the polyimide prepared in Comparative Example 1 is used in step 1, and the remaining steps and parameters remain the same.
[0086] Comparative Example 4
[0087] A method for preparing a polyimide separator for a lithium battery is different from that of Example 5 in that the polyimide prepared in Comparative Example 2 is used in step 1, and the remaining steps and parameters remain the same.
[0088] Comparative Example 5
[0089] A method for preparing a polyimide diaphragm for a semi-solid lithium battery, which differs from Example 5 in that the fast ion conductor lithium lanthanum zirconium oxide is not added in step 1, and the other steps and parameters remain the same.
[0090] The performance of the polyimide separators for lithium batteries prepared in Examples 5 to 8 and Comparative Examples 3 to 5 was tested, and the test results are shown in Tables 2 and 3:
[0091] Table 2
[0092] Thickness(μm) Porosity (%) Air permeability (s / 100mL) Puncture strength (gf) Example 5 12.0 55 120 275 Example 6 12.5 52 134 284 Example 7 11.8 56 107 281 Example 8 12.6 59 94 268 Comparative Example 3 12.1 52 78 231 Comparative Example 4 12.2 51 77 227 Comparative Example 5 12.4 53 118 262
[0093] Table 3
[0094]
[0095] The diaphragms prepared in Examples 5 to 8 and Comparative Examples 3 to 5 were cut into sizes matching the 40 mm × 60 mm metal plates, assembled into soft-pack batteries, injected with electrolyte, tested the AC impedance, and then placed in 1-4 layers of diaphragms in sequence, tested the resistance value, and plotted a curve with the number of diaphragm layers as the abscissa and the diaphragm resistance as the ordinate. The slope of the curve is the ionic conductivity, which can characterize the migration ability of lithium ions in the diaphragm. The test results are shown in Table 4:
[0096] Table 4
[0097] Ionic conductivity (mS / cm) Example 5 1.84 Example 6 1.79 Example 7 1.66 Example 8 1.67 Comparative Example 3 1.49 Comparative Example 4 1.41 Comparative Example 5 1.27
[0098] It can be seen from Tables 2 to 4 that the thickness of the polyimide separator for semi-solid lithium batteries prepared by the present invention is 12±1 μm; the porosity is 55±5%; the air permeability reaches 120±40s / 100mL, and the puncture strength is ≥200gf; the tensile strength MD≥200Mpa, TD≥15Mpa; the elongation at break MD≥50%, TD≥200%; the thermal shrinkage rate (120℃ / 1h) MD≤1%, TD≤0.5%; it has excellent performance and high ionic conductivity.
[0099] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0100] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polyimide separator for a semi-solid lithium battery, characterized in that: It includes a polypropylene base film and a gel polyimide coating layer arranged on both sides of the polypropylene base film, wherein the gel polyimide coating layer is made by spraying a fast ion conductor modified polyimide slurry; The fast ion conductor modified polyimide slurry comprises the following components in parts by weight: 3.5-4.5 parts of thermoplastic polyimide; 1-3 parts of lithium bis(trifluoromethanesulfonyl)imide; Fast ion conductor lithium lanthanum zirconium oxide 0.8-1.2 parts; Sulfolane 35-45 parts.
2. A polyimide separator for a semi-solid lithium battery according to claim 1, characterized in that: The chemical structural formula of the thermoplastic polyimide is Formula I: Where x = 60-80%; Where R is Any one of the following, wherein n is any integer between 0 and 5, and R1 and R2 are -H or -CH3.
3. A polyimide separator for a semi-solid lithium battery according to claim 1, characterized in that: The polypropylene-based film has a melt flow rate of 0.3-0.5 g / 10 min, a tensile strength of 200-240 MPa, a pore size of 50-110 nm, and a porosity of 50-55%.
4. A method for preparing a polyimide separator for a semi-solid lithium battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, under stirring conditions, adding thermoplastic polyimide to sulfolane, reacting at 140-160° C. for 1-3 hours, then adding lithium bis(trifluoromethanesulfonyl)imide and fast ion conductor lithium lanthanum zirconium oxide in sequence, and continuing the reaction for 1-3 hours to obtain a fast ion conductor modified polyimide slurry; Step 2, performing corona treatment on the surface of the polypropylene base film; Step 3: spray the fast ion conductor modified polyimide slurry on the surface of the polypropylene base film after corona treatment, and vacuum dry it to obtain a polyimide separator for a gel semi-solid lithium battery.
5. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 4, characterized in that: The preparation method of the thermoplastic polyimide comprises the following steps: S1. Under nitrogen protection and ≤5°C, 4,4'-diaminodiphenyl ether and pyromellitic anhydride are sequentially added to N,N-dimethylacetamide to react to obtain an amino-terminated polyamic acid prepolymer A with a low degree of polymerization; S2. Under nitrogen protection and ≤5°C, 4,4'-diaminodiphenyl ether and diphenyl diglycoside compound are sequentially added to N,N-dimethylacetamide to react to obtain a low polymerization degree terminal anhydride polyamic acid prepolymer; S3. The amino-terminated polyamic acid prepolymer A and the anhydride-terminated polyamic acid prepolymer B are uniformly mixed and subjected to a condensation reaction to obtain a polyamic acid solution; S4. Under stirring conditions at room temperature, add an imidization reagent to the polyamic acid solution, mix well, heat to 35-45°C and continue to react for 15-20 hours to obtain a polyimide solution, cool to room temperature, add ethanol for precipitation, collect the precipitate, and vacuum dry to obtain a thermoplastic polyimide.
6. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 5, characterized in that: The molar ratio of the anhydride in pyromellitic anhydride to the amino group in 4,4'-diaminodiphenyl ether is 1:(1.2-1.5), and the solid content in the reaction system is 25-35%.
7. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 5, characterized in that: The chemical structural formula of the diphenyl diglycoside compound is Formula IV: Where R is Any one of the following, wherein n is any integer between 0 and 5, and R1 and R2 are -H or -CH3.
8. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 5, characterized in that: The molar ratio of the acid anhydride in the diphenyl diglycoside compound to the amino group in 4,4'-diaminodiphenyl ether is 1:(1.2-1.5), and the solid content in the reaction system is 25-35%.
9. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 5, characterized in that: The imidization reagent is composed of acetic anhydride and triethylamine mixed in a molar ratio of 1:
1.
10. The method for preparing a polyimide separator for a semi-solid lithium battery according to claim 5, characterized in that: The molar ratio of the imidization reagent to the total amount of 4,4'-diaminodiphenyl ether is 1:(0.2-0.8).
Citation Information
Patent Citations
Composite diaphragm as well as preparation method and application thereof
CN117458083A
Preparation method of polyimide-based composite diaphragm for lithium battery
CN118783028A